Tests and criteria for assessing the anaerobic workability of sprinter athletes - A.G. Samborskiy; S.N. Severin; E.S. Nikolaeva; G.L. Nesterenko (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the effect of multiple maximum power exercises on the anaerobic performance of sprinters. Methods and structure of the study. The experiment involved 11 sprinters of qualification Candidate for Master of Sports and I category. To assess anaerobic performance in the laboratory, athletes underwent repeated bicycle ergometric tests in the test of maximum anaerobic power (MAP). In the field, to study the dynamics of speed in sprinting, the subjects completed a ten-fold run of a distance of 60 m from a low start at full strength after 1 min of rest. Results and conclusions. The maximum speed in sprinting is reached at the sixth second from the start. During this time, oxidative processes in the tissues practically do not have time to unfold to a significant extent. This time is not enough for a significant increase in anaerobic glycolysis in working muscles. The energy supply of maximum muscle activity in these first 5-6 seconds is carried out mainly due to the alactic anaerobic process, that is, due to the breakdown of intramuscular reserves of organophosphorus compounds ATP and creatine phosphate. At the same time, as a result of multiple repetitions of maximum power exercises, a very strong acidification of the intramuscular environment occurred, which led to a decrease in the leading criteria for sprint performance.